Preparing for Clinical Laboratory Improvement Amendments (CLIA) and College of American Pathologists (CAP) Inspections. Issue 12 (27th December 2021) - Zneimer, Susan M.; Hongo, Donna
Abstract: Clinical laboratories have many regulations to follow, requiring complete adherence to specific standards and regulations in order to be granted accreditation. As part of the accreditation process, a laboratory must be inspected. Whether it is an initial or biennial inspection, there are some standard tasks and duties a laboratory can do to prepare in advance to reduce stress, improve the inspection process, and reduce the risk of getting a deficiency. Good Clinical Laboratory Practice (GCLP) is an important part of preparing a clinical laboratory for Clinical Laboratory Improvement Amendments (CLIA) and College of American Pathologists (CAP) inspections. GCLP standards have been developed by CLIA and were developed with the goal of providing a sole source of requirements that clinical laboratories using human patient samples need to follow to ensure reproducible and reliable clinical laboratory results. The Laboratory Accreditation Program (LAP) of the College of American Pathologists (CAP) also has ongoing activities and guidelines for clinical laboratories to follow. Although this is a voluntary program, it is driven by peer review, education, and compliance to established performance standards. CAP is focused on laboratory improvement and views its inspections as collaborations between inspector and laboratory. The CAP checklists, based on their standards for good lab practice, are used by inspectors to ensure that each inspection is consistent and thorough and to enable CAP to determine if the laboratory meets the standards for accreditation. © 2021 Wiley Periodicals LLC.